Political trust and public support for propaganda in China - Haifeng Huang; Chanita Intawan; Stephen P. Nicholson (Research & Politics, 2024)
Authoritarian governments heavily rely on propaganda as a means of maintaining rule. Although scholars have examined the effects of propaganda exposure, much less is known about attitudes toward propaganda messages. In this study, we explore the foundations underlying propaganda support in China by examining the role of political trust, a primary ingredient for explaining public support for government actions and compliance. Using a survey with a broad sample of Chinese internet users and taking measures to address endogeneity, we found that trust in government, whether measured indirectly (implicitly) or directly (explicitly), is a vital source of positive attitudes toward propaganda and hence its potential effects. Our results have important implications for understanding the foundations of propaganda support, the scope of political trust, and the value of indirect measures for gauging public opinion in authoritarian contexts. They also suggest that propaganda may lose its bite under certain conditions.